Empowerment of youth posyandu cadres as an effort to delay the age of marriage and prevent teenage pregnancy - Hapisah; Rusmilawaty; Rafidah (Abdimas Polsaka, 2025)
Early marriage and teenage pregnancy remain serious public health issues, as they impact the health of mothers and babies, as well as the social and economic well-being of families. In this regard, integrated health service post (Posyandu) cadres play a crucial role as the spearhead of health education, particularly in providing accurate information to adolescents. This community service program aimed to increase the understanding of adolescent Posyandu cadres, toddler Posyandu cadres, and young women regarding the importance of maturing marriageable age and efforts to prevent teenage pregnancy. The program involved 25 adolescent Posyandu cadres, toddler Posyandu cadres, and young women from Simpang Warga Village, Aluh-Aluh District, Banjar Regency. The implementation phase included a pretest, interactive lecture presentation, a question-and-answer discussion, and a case study related to the phenomenon of teenage pregnancy. A posttest and field evaluation were then conducted to assess the extent of the material's implementation. The data obtained were analyzed descriptively to measure the increase in participants' knowledge. The results showed an increase in average knowledge scores after the intervention. The integrated health post (Posyandu) cadres also demonstrated their readiness to apply the material in youth Posyandu activities, particularly in providing education on the health risks of early marriage. Overall, this community service program has proven effective in strengthening the capacity of Posyandu cadres to support the movement to increase the age of marriage and prevent teenage pregnancy. For the program's sustainability, cross-sector collaboration, including with village governments and community health centers, is needed to strengthen promotive and preventive efforts at the community level